The Role Of Organizational Culture In Enhancing Employee Performance In Start-Up Companies - Sihombing, Tulus Martua (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2024)
Organizational culture plays a crucial role in determining employee performance, especially within the context of start-up companies that face unique and dynamic challenges. This study aims to explore how organizational culture can enhance employee performance in start-ups, as well as the key factors that support the effectiveness of such culture. Through a literature review and empirical analysis, it was found that an inclusive, collaborative, and innovative organizational culture significantly contributes to increased productivity, job satisfaction, and employee loyalty. In start-up companies, where organizational structures are often flatter and work processes more flexible, a culture that encourages openness and adaptation to change becomes critical. Additionally, leadership that can instill core company values and support the development of individuals and teams further strengthens employee engagement with the organization. These factors, when implemented effectively, not only improve individual performance but also drive the overall sustainability and growth of the company. This study concludes that start-ups must consciously build and manage their organizational culture to achieve optimal performance. These findings are expected to serve as a guide for managers and founders of start-up companies in designing effective organizational culture strategies to maximize employee potential and achieve long-term business goals.